Uniform Crime Reporting Program Data (United States): Offenses Known and Clearances by Arrest in All Cities with Populations Over 250,000, 1987-1988 ([Verlag nicht ermittelbar], 1990)
Since 1930, the Federal Bureau of Investigation has compiled the Uniform Crime Reports (UCR) to serve as periodic nationwide assessments of reported crime not available elsewhere in the criminal justice system. Each year, this information is reported in four types of files: (1) Offenses Known and Clearances by Arrest, (2) Property Stolen and Recovered, (3) The Supplementary Homicide Reports (SHR), and (4) Police Employee (LEOKA) data. This collection contains Offenses Known and Clearances by Arrest data and includes monthly information on the number of Crime Index offenses reported, the number of offenses cleared by arrest or other means, and the number of adults and juveniles arrested in cities with populations over 250,000. The counts include all reports of Index Crimes (excluding arson) received from victims, from officers who discovered infractions, or from other sources.